A Novel Manufacturing Technology for RF MEMS Devices on Ceramic Substrates. (23rd November 2010) - Schirosi, V.; Del Re, G.; Ferrari, L.; Caliandro, P.; Rizzi, L.; Melone, G.
Abstract : Microelectromechanical systems are often used for their enormous capability and good qualities in T/R modules especially for space modular applications. High isolation and very low insertion loss are guaranteed by their intrinsic working principle. This is a very robust, flexible, and low-cost technology, and it provides high reliability, good reproducibility, and complete fulfillment of technical requirements.